IMPACT OF AGRICULTURAL POLICY ON EGYPTIAN RICE - Moataz Eliw; Samim S. Alim; Sarhan A. Soliman (Journal of Animal and Plant Sciences, 2022)
Egypt is the largest rice producer in the Middle East, with total production accounting for 1.25% of the world's rice production. Rice is considered as an important export crop and a source of hard currency earnings required to finance sustainable economic and social development. In 2016, rice exports value amounted to US$ 24.277 million. To achieve the research objective, rice production and economic indicators were estimated by applying simple regression analysis, as well as partial equilibrium model based on two scenarios; under governmental intervention and under non-intervention by the government in order to assess the economic impacts of interventions in pricing and production policies. The research used field data a multistage stratified sample collected from 256 rice farmers in Kafr El Sheikh governorate to identify farmers’ opinions regarding agricultural policies applied to the crop and the different impacts thereof. the results showed that the rice production declined at a rate lower than the rate of decline in planted area, which can be attributed to the increase in yield. Also, domestic rice consumption increased at a high rate that reached 2.76% per annum despite the decline in production that reached 1.92% per annum, the nominal protection coefficient recorded an average of 0.6 for the study period 2001-2018, which means that the government has been imposing either direct or indirect taxes on domestic rice producers in favor of consumers, where farmgate price has been lower than the border price of rice. The problem that rice production is influenced by limiting rice planted area ranks first, with a relative importance amounting to 100%. Low productivity ranks second, with a relative importance amounting to 96.88%.
Keywords: Agricultural Policy; Partial Equilibrium Model; Production; Egyptian Rice